Conduction system pacing with AV node ablation versus catheter ablation for treatment of persistent atrial fibrillation in patients with heart failure with reduced ejection fraction. (19th May 2022) - Rauber, M; Ivanovski, M; Klemen, L; Zupan Meznar, A; Pernat, A; Jan, M; Zizek, D; Antolic, B
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: In patients with persistent atrial fibrillation (PeAF) and heart failure with reduced ejection fraction (HFrEF) current guidelines recommend treatment of AF with catheter ablation (CA) (1). Recurrence of either AF or atrial flutter, often requiring additional procedures, are not uncommon, thus optimal long-term treatment of these patients is still unknown. Recently conduction system pacing (CSP), with more physiological ventricular activation, has made the ''pace and ablate'' strategy an attractive alternative for the treatment of PeAF refractory to medical therapy (2). Purpose: Long term data comparing CA with conduction system pacing and AV node ablation (CSP/AVNa) for treatment of patients with PeAF and HFrEF is lacking. Hence, we sought to compare clinical outcomes of both treatment modalities. Methods: In a retrospective study consecutive patients under 75 years of age, with PeAF and left ventricular ejection fraction (LVEF) less than 50%, treated with CSP/AVNa from 2018 to 2021 in UMC Ljubljana were included. A control patient treated with CA for PeAF matched in age, sex and LVEF was assigned for each included CPS/AVNa patient. Both groups were compared for procedure-related characteristics, echocardiographic parameters, hospitalisations for heart failure and all-cause mortality. Results: Among 771 patients referred for interventional treatment of AF, 23 patients treated with CSP/AVNa were included and compared with 23 CA matched controls. The general characteristics of both groups are summarised in Table 1. The mean follow-up was 20 ± 10 and 21 ± 8 months for CPS/AVNa and CA group, respectively (p=0.76). In CPS/AVNa group 83% received his bundle pacing and 17% left bundle branch area pacing. A selective CSP was achieved in 43% of CSP/AVNa patients. In addition to pulmonary vein isolation, additional ablation lines were performed in 35% of patients in the CA group. Significant improvement in LVEF was observed in both groups, 12% ± 11% (p<0.001) in CSP/AVNa and 21% ± 12% (p<0.001) in CA group. Hospitalisations for HF were rare during the follow-up, with 9% in CSP/AVNa and 4% in the CA ablation group (p=0.561). All-cause mortality was 9% in CSP/AVNa and 0% in CA group (p=0.153). However, major comorbidities were more common in the CSP/AVNa group than in the CA group, 3.4 ± 1.6 and 2.3 ± 1.5, respectively (p=0.017). Procedure-related characteristics are summarised in Table 1. In each group, 2 minor procedure-related adverse events were observed: 2 acute rises in pacing threshold post-AVNa in CSP/AVNa group and puncture site hematoma and transient pericardial effusion in CA group. Conclusion: In patients with PeAF and HFrEF, CSP/AVNa treatment strategy seems to derive similar clinical outcomes compared to CA approach. Larger prospective randomised data are needed to further confirm these initial findings and determine optimal long-term treatment strategy for this group of patients.